PENANGANAN KELUHAN PELANGGAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEMEN GRESIK - ZAINAL ARIFIN (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
If customer complaints positively responded to and will be served can bring benefits to the company. In excellent service is the handling of customer complaints is paramount. This study aims to determine the handling of customer complaints on customer loyalty through customer satisfaction.This research is a survey with path analysis approach. The study was conducted in PT Semen Indonesia (Persero) Tbk. with a population of corporate agency business customers of PT Semen Indonesia (Persero) Tbk. in the province of East Java as many as 125 companies. Samples were taken with the technique of proportional random sample of respondents earned by 95 companies. Data taken with the questionnaire, further analysis of the data using path analysis.The results showed t count for variable handling of complaints by 2,295> t table (1.987) means that there is an influence significantly the handling of complaints terhadapa customer satisfaction. Then t count for the handling of complaints by 3.490, t count of 3,010 for customer satisfaction both> t table (1.987), mean variables complaint handling and customer satisfaction have a significant effect on customer loyalty. Whereas the effect on customer loyalty penangann complaint through customer satisfaction by 0.093, meaning that any increase in the handling of customer complaints through customer satisfaction by 1 point it will increase customer loyalty by 0.093 points.Based on the results of the study are expected PT Semen Indonesia (Persero) Tbk to improve its services by creating the same type of products but the specs match the needs of its customer segmentation and customer complaints to improve services in order to improve customer satisfaction so far maintained loyalty. For customers expected to use Gresik cement products as per the specifications and designation and submit complaints directly to the officer of PT Semen Indonesia (Persero) Tbk appropriate existing mechanisms.